APLICAÇÃO DE ZEÓLITAS COMO ALTERNATIVA PARA MINORAR EFEITOS DO ESTRESSE SALINO EM Ixora coccínea L. - de Sousa, humberto Gildo; Feitosa de Lacerda, Claudivan; Damasceno da Silva, Lindomar Roberto; Ferreira de Medeiros, Wiliana Júlia; Santos Cavalcante, Eduardo; Mendonça de Sousa, Alfredo (Comunicata Scientiae, 2023)
Zeolites are crystalline aluminosilicates with cation adsorption capacity in soils and waters. In this context, the objective was to evaluate the potential of a synthetic type A zeolite, applied to the substrate, to reduce the extraction of Na + by plants of the ornamental species Ixora coccínea L., and, consequently, to mitigate the negative effects of salinity on physiology and in the growth of this species. The research was carried out in a greenhouse, from April to June 2018. The experiment was carried out under a randomized block design, in a 4 × 2 factorial scheme, corresponding to four levels of electrical conductivity of the irrigation water - CEa ( 0.6, 2.0, 3.4 and 5.0 dS m-¹), with the presence and absence of zeolite and four repetitions. The salinity of the irrigation water had deleterious effects on the ornamental species I. coccínea, causing reductions in leaf gas exchange, flower production and plant growth. No accumulation of Na + was observed in the leaf tissues, suggesting that the negative effects of salinity were mainly associated with the osmotic component of salt stress. Interaction between salinity and zeolites was observed for the production of aerial and total biomass, however, there was low sodium accumulation in the leaves, which made it impossible to conclude about any beneficial effect of zeolite in I. coccínea under salt stress.